Social work students' perspective on environmental justice: Gaps and challenges for preparing students. Issue 3 (2nd October 2019) - Decker Sparks, Jessica L.; Combs, Katie Massey; Yu, Jennifer
ABSTRACT: The integration of environmental justice into social work education, research, and practice has grown substantially in the past decade. However, social workers still report feeling unprepared to address these challenges with their clients and communities. To understand the disconnect between education about and application of environmental justice principles, semi-structured qualitative interviews were conducted with graduate social work students (n = 14). Findings suggest this disconnect is catalyzed, in part, by the environment's meta nature and a lack of facilitated education on the dynamic feedbacks between the physical environment and social justice issues. Implications for social work educators are discussed.